2001
DOI: 10.1136/heart.86.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic ST segment elevation in right precordial leads with right bundle branch block (Brugada-type ST shift) among the general Japanese population

Abstract: Objective-To examine the modality and morbidity of asymptomatic ST segment elevation in leads V1 to V3 with right bundle branch block (Brugada-type ST shift). Methods-8612 Japanese subjects (5987 men and 2625 women, mean age 49.2 years) who underwent a health check up in 1997 were investigated. Those with Brugada-type ST shift underwent the following further examinations over a two year period after the initial check up: ECG, echocardiogram, 24 hour Holter monitoring, treadmill exercise testing, signal average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
4
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 22 publications
(23 reference statements)
7
64
4
3
Order By: Relevance
“…In keeping with previous reports,4, 7, 9, 10, 21, 22 there was a male predominance among participants with BrS. In the present study, no SCD among participants with type 1 BrS and only 1 SCD among those with non–type 1 BrS was observed during the follow‐up period, which was consistent with previous community‐based studies,6, 8, 9, 12, 14 except for the Atomic Heart Study 11.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In keeping with previous reports,4, 7, 9, 10, 21, 22 there was a male predominance among participants with BrS. In the present study, no SCD among participants with type 1 BrS and only 1 SCD among those with non–type 1 BrS was observed during the follow‐up period, which was consistent with previous community‐based studies,6, 8, 9, 12, 14 except for the Atomic Heart Study 11.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of type1 BrS (0.1%) and non–type 1 BrS (1.2%) in this cohort was compatible with that in previous studies: 0.0% to 0.2%5, 6, 7, 8, 9, 10, 12, 13, 14, 19 for type 1 BrS and 0.0% to 6.0% for non–type 1 BrS 4, 5, 7, 9, 10, 13, 14, 20. In keeping with previous reports,4, 7, 9, 10, 21, 22 there was a male predominance among participants with BrS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a Japanese urban population, the frequency in males was found to be 0.38% for the coved type and 2.14% for the saddleback type. 8) Furuhashi, et al 9) reported the frequency of ST segment elevation as 0.14% in 8612 asymptomatic subjects with a mean age of 49 years. In recent years, the frequency of Brugada sign has been reported to range between 0.14-0.70% in middle-aged healthy populations.…”
Section: Frequency Of Brugada Signmentioning
confidence: 99%
“…The indications (primary and secondary prevention) of ICD in specific disorders are shown in Table 2. The prognosis of patients with Brugada syndrome is controversial especially in asymptomatic patients (48)(49)(50). Their prognosis seems good in Japan (51 From Japanese Joint Guidelines of Nonpharmacological Therapy of Cardiac Arrhythmias (34).…”
Section: Primary Prevention Of Scdmentioning
confidence: 99%